Analisis Sejarah Kolonialisme Belanda dalam Perkembangan Orientalisme di Indonesia - Mohammad Djaya Aji Bima Sakti; Muhammad Nurrosyid Huda Setiawan; Alhafidh Nasution; Amar Ramadhan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2024)
This research aims to analyze the relevance and influence of Dutch colonialism and it’s relevant to the development of orientalism in Indonesia. By using the ideas of the theory of orientalism that was promoted by Edward Said, this research will attempt to explore how Dutch colonialism has influenced and shaped cultural patterns with a shifting of paradigm and had the impact of changing identity in Indonesia for a long time. Through a qualitative approach, this research seeks to analyze Dutch colonial impact and legacies and tries to reveal the strategies by which these Orientalist though are still indirectly practiced today. This research provides an illustration that orientalism and colonialism are two interrelated interests and have had quite a dominant influence in the history of these two organizations in Indonesia. Colonialism became the initial basis for the orientalism movement to develop, because with its presence, orientalism could freely carry out several goals and orientations of its movement, which included Christianization and westernization.